2017
DOI: 10.1590/0366-69132017633682193
|View full text |Cite
|
Sign up to set email alerts
|

Influência da variação da velocidade de rotação e do tipo de cimento nas propriedades de argamassas de revestimento nos estados fresco e endurecido

Abstract: ResumoA etapa de mistura influencia as condições de execução do revestimento de argamassa, visto que desde o primeiro contato dos materiais sólidos com água uma série de eventos de aglomeração e desaglomeração no sistema é verificada. Acontece que durante o processamento das argamassas em obra a utilização de equipamentos com distintos mecanismos de mistura pode modificar o desempenho do sistema de revestimento. Este trabalho foi realizado com o objetivo de avaliar a influência da condição de mistura durante o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…In the case of cellulose waste, CENIBRA Institute (Celulose Nipo-Brasileira) reported that, on average, each ton of cellulose produced generates 200 kg of solid waste, half of which is inorganic solid waste (dregs, grits, and lime mud) [4]. Some researches on waste from foundry industry have focused on DFSs due to their high volume (86% of generated waste [5]) and also to the various applications, such as utilization as aggregate in the manufacture of Portland cement concrete [6], and road paving [7,8]. Some works report the use of foundry waste, either without separation or mixed with other residues [9][10][11][12][13][14].…”
Section: (Utilização De Areia Descartada De Fundição (Adf) E Resíduos Inorgânicos Da Indústria De Papel E Celulose Para a Produção De Matmentioning
confidence: 99%
“…In the case of cellulose waste, CENIBRA Institute (Celulose Nipo-Brasileira) reported that, on average, each ton of cellulose produced generates 200 kg of solid waste, half of which is inorganic solid waste (dregs, grits, and lime mud) [4]. Some researches on waste from foundry industry have focused on DFSs due to their high volume (86% of generated waste [5]) and also to the various applications, such as utilization as aggregate in the manufacture of Portland cement concrete [6], and road paving [7,8]. Some works report the use of foundry waste, either without separation or mixed with other residues [9][10][11][12][13][14].…”
Section: (Utilização De Areia Descartada De Fundição (Adf) E Resíduos Inorgânicos Da Indústria De Papel E Celulose Para a Produção De Matmentioning
confidence: 99%
“…On the other hand, the hysteresis loop indicates that the finer particles and the surface areas tend to cause agglomeration in the cementitious system, which, with the increase of shear condition, were broken during an acceleration step imposed in the test. However, with deceleration, a re-agglomeration rate is not as pronounced as the disruption of the agglomerates [33].…”
Section: Correlation Between the Torque And Shear Conditionmentioning
confidence: 94%
“…The calculated area under the curves of Figure 4 indicates an estimative of the energy needed for the adequate mixing of each grout. The results are shown in Figure 5, with the graph produced as the function of the consumption of binder in each composition [33]. This comparative evaluation is valid only for the same mixing conditions applied in this work.…”
Section: Mixing Stagementioning
confidence: 95%